Choline: An Essential Nutrient for Skeletal Muscle - Moretti, Antimo; Paoletta, Marco; Liguori, Sara; Bertone, Matteo; Toro, Giuseppe; Iolascon, Giovanni (Nutrients, 2020)
Background: Choline is an essential micronutrient with a pivotal role in several metabolic pathways contributing to liver, neurological, and hematological homeostasis. Although choline is commonly administered to improve physical performance, its effects on muscle are still unclear. The aim of this scoping review is to analyze the role of choline on skeletal muscle in terms of biological effects and clinical implications. Methods: A technical expert panel (TEP) of 6 medical specialists with expertise in muscle physiology and skeletal muscle disorders performed the review following the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews) model. The TEP planned a research on PubMed selecting “choline” as MeSH (Medical Subject Headings) term adding to PubMed Search Builder the terms ”skeletal muscle” and “muscle striated”. TEP considered for eligibility articles published in the last 30 years, including original researches, particularly in vitro studies, and animal and clinical studies in the English language. Results: From the 1239 studies identified, TEP included 14 studies, 3 in vitro, 9 animal, and 2 clinical studies. Conclusions: Our scoping review elucidates and summarizes the crucial role of choline in modulating muscle fat metabolism, muscle proteins homeostasis, and the modulation of inflammation and autophagy.